Dari Media Sosial hingga Ingatan Konsumen: Peran Strategi Digital Marketing dalam Meningkatkan Kesadaran Merk UMKM Sate Bulayak Inaq Renah, Kecamatan Narmada Kabupaten Lombok Barat - Ratu Marliana Ma’idah; Siti Atika Rahmi; Abdul Hafiz (Economic Reviews Journal, 2026)
This research explores the role of digital marketing strategies in building brand awareness for the micro, small, and medium enterprise (MSME) Sate Bulayak Inaq Renah in Narmada District, West Lombok. The digital era has transformed promotional methods, pushing MSMEs to leverage online platforms to remain relevant and expand their customer base. However, many traditional culinary businesses still struggle to maximize these digital tools due to informal marketing approaches and limited strategic planning. This study employs a qualitative descriptive method, gathering data through in-depth interviews with business owners, staff, and consumers. The analysis reveals that Sate Bulayak Inaq Renah utilizes platforms like TikTok, Facebook, and WhatsApp to organically reach audiences. This digital exposure significantly enhances brand awareness, moving consumers from a state of unawareness to brand recall and eventually top-of-mind status. The findings suggest that while digital marketing is a powerful catalyst for visibility, sustained brand awareness relies heavily on product quality and authentic consumer engagement. The findings reveal that all four dimensions of digital marketing have been implemented, although they are not yet managed through a formalized strategy. These digital marketing activities have been shown to contribute to the movement of consumers from a state of being unaware of the brand toward achieving the top-of-mind level of brand awareness. However, the effectiveness of these strategies remains highly dependent on consistent product quality and the strength of personal relationships established between the business and its consumers. This study highlights that digital marketing in traditional culinary MSMEs functions as an accelerator rather than the sole determinant in developing sustainable brand awareness.